Ocean Acidification-Induced Restructuring of the Plankton Food Web Can Influence the Degradation of Sinking Particles - Stange, Paul; Taucher, Jan; Bach, Lennart T.; Algueró-Muñiz, María; Horn, Henriette G.; Krebs, Luana; Boxhammer, Tim; Nauendorf, Alice K.; Riebesell, Ulf (Frontiers in Marine Science, 2018)
Ocean acidification (OA) is expected to alter plankton community structure in the future ocean. This, in turn, could change the composition of sinking organic matter and the efficiency of the biological carbon pump. So far, most OA experiments involving entire plankton communities have been conducted in meso- to eutrophic environments. However, recent studies suggest that OA effects may be more pronounced during prolonged periods of nutrient limitation. In this study, we investigated how OA-induced changes in low-nutrient adapted plankton communities of the subtropical North Atlantic Ocean may affect particulate organic matter (POM) standing stocks, POM fluxes, and POM stoichiometry. More specifically, we compared the elemental composition of POM suspended in the water column to the corresponding sinking material collected in sediment traps. Three weeks into the experiment, we simulated a natural upwelling event by adding nutrient-rich deep-water to all mesocosms, which induced a diatom-dominated phytoplankton bloom. Our results show that POM was more efficiently retained in the water column in the highest CO2 treatment levels (> 800 µatm pCO2) subsequent to this bloom. We further observed significantly lower C:N and C:P ratios in post-bloom sedimented POM in the highest CO2 treatments, suggesting that degradation processes were less pronounced. This trend is most likely explained by differences in micro- and mesozooplankton abundance during the bloom and post-bloom phase. Overall, this study shows that ocean acidification can indirectly alter POM fluxes and stoichiometry in subtropical environments through changes in plankton community structure.